ChemInform Abstract: Catalytic Oxidation of Soot over Alkaline Niobates. Issue 14 (20th March 2013) - Pecchi, G.; Cabrera, B.; Buljan, A.; Delgado, E. J.; Gordon, A. L.; Jimenez, R.
Abstract MNbO3 powders (M: Li, Na, K, Rb) are synthesized by a citrate method and calcined at 450, 550, 650, and 750 °C.